The unintended consequences of confinement: Evidence from the rural area in Guatemala - Castillo, Jose Gabriel; Hernandez, Manuel A. (Elsevier, 2023)
Individual and social preferences have shown to be important factors in individual decision making and general economic performance. Yet, they are usually assumed as given and stable, underestimating their impact in the rhythm of economic recovery after a natural disaster or pandemic. This paper examines the effects of COVID-19 initial confinement on households’ individual and social preferences across small communities in the rural area of Guatemala. We use a comprehensive panel household survey of agricultural smallholders collected during two survey rounds in 2019, prior to the pandemic, and 2020 and find that preferences generally shifted following the onset of the pandemic. We observe a significant increase in risk tolerance, deteriorated perceptions towards trust and generosity, and a higher frequency of emotional issues, while intra-household relationships remain stable. We find that experiencing a household adverse situation, a higher degree of exposure to the virus, and more stringent local confinement measures shaped several of the variations in preferences. The focus of the study on a region with high poverty and malnutrition rates offers important insights of the consequences of confinement on perceptions and attitudes in complex and vulnerable rural contexts during the wake of a public health emergency.